2021
DOI: 10.1007/s10096-021-04302-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and utility of facemask sampling in the detection of SARS-CoV-2 during an ongoing pandemic

Abstract: s Easy access to screening for timely identification and isolation of infectious COVID-19 patients remains crucial in sustaining the international efforts to control COVID-19 spread. A major barrier limiting broad-based screening is the lack of a simple, rapid, and cost-effective COVID-19 testing method. We evaluated the feasibility and utility of facemask sampling in a cohort of 42 COVID-19-positive and 36 COVID-19-negative patients. We used a prototype of Steri-Strips™ (3 M) applied to the inner s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Previous studies using sampling from modified facemasks have not assessed longitudinal RNA VL kinetics. [5][6][7][8][9]12] Our findings are consistent with findings from the Gesundheit II-exhaled breath collector (GII). [19] Here, higher RNA VL were observed in exhaled breath within those who were sampled once, on day 3 after symptom onset.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies using sampling from modified facemasks have not assessed longitudinal RNA VL kinetics. [5][6][7][8][9]12] Our findings are consistent with findings from the Gesundheit II-exhaled breath collector (GII). [19] Here, higher RNA VL were observed in exhaled breath within those who were sampled once, on day 3 after symptom onset.…”
Section: Discussionsupporting
confidence: 87%
“…While there are single point assessments of exhaled virus by different methods, no clear picture exists of the natural history of SARS-CoV-2 emission. [4][5][6][7][8] Facemask sampling (FMS) offers particular advantages for assessment of exhaled virus output over multiple sampling periods. [9] FMS can be performed within the comfort of patients' own homes and the methodology is replicable in most routine laboratories.…”
Section: Introductionmentioning
confidence: 99%
“… Exhaled aerosols Analytes Types of facemasks Detection limits Analytical approaches Ref. Bacteria Mycobacterium tuberculosis FFP3 facemask 100-100 qPCR [ 28 ] CFU Mycobacterium tuberculosis N95 facemask Ct value: 29 qPCR [ 31 ] Antimicrobial resistance genes Modified FFP1 facemask with gelatin filter Ct value:100 qPCR [ 32 ] Unspecified Bacteria Surgical facemask loaded with 3D-PVA NA Unspecified [ 33 ] Viruses Rhinovirus, Influenza A virus, and Parainfluenza virus Homemade facemask by PVA NA PCR [ 41 ] Bacillus atrophaeus, Bacteriophage MS2 Homemade by cotton t-shirt fabric and surgical mask NA Henderson apparatus [ 42 ] SARS-CoV-2 Modified cup-type N95 mask with a gelatin membrane Ct value: 27.29 RT-PCR [ 48 ] SARS-CoV-2 Modified duckbilled surgical facemask containing 3D-PVA ≤999 copies/strip RT-qPCR [ 49 ] SARS-CoV-2 Surgical facemasks with three Steri-Strips Ct value: 25.2 RT-qPCR [ 50 ] SARS-CoV-2, HCov-NL63 CPAP-type 10 to 100 copies/flte RT-qPCR [ 51 ] Proteins Cytokines Hard-surface plastic masks, disposable hospital paper masks NA ICA ...…”
Section: Facemask Sapling Of Human Exhaled Aerosolsmentioning
confidence: 99%
“…Williams et al [ 49 ] collected exhaled SARS-Cov-2 by wearing facemask ( Figure 4 d) and found a potentially significant relationship between facemask sampling and nasopharyngeal swabs viral load which demonstrated a pick-up rate of 65-70% in those which were concomitantly nasopharyngeal swabs positive. Ng et al [ 50 ] systematically evaluated the feasibility of facemask for detecting exhaled SARS-CoV-2, showing that facemask sampling had a pick-up rate of 62.6-87.5% of patients who were tested within the first 5 days of symptom onset. Moreover, Smolinska et al [ 51 ] developed filter-modified CPAP-type face mask to capture exhaled virus particles.…”
Section: Facemask Sapling Of Human Exhaled Aerosolsmentioning
confidence: 99%
See 1 more Smart Citation